2021
DOI: 10.2224/sbp.10213
|View full text |Cite
|
Sign up to set email alerts
|

Residents' intention to take collective action through participation in not-in-my-backyard protests in China

Abstract: Using the theory of planned behavior, we investigated the factors motivating residents' intention to take collective action by participating in not-in-my-backyard protests. We conducted a survey with 286 Chinese residents living near a waste-to-energy incineration plant. Results of structural equation modeling show that the personal factors of attitude, subjective norm, and self-efficacy positively affected intention to protest. Perceived group size (in-group factor) indirectly and directly affected intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Drawing from the Theory of Planned Behavior (Ajzen, 1985), which postulates that behavioral intentions need to be formed before individuals perform a behavior, it can be expected that environmental behavior intentions function as a predictor for subsequent behavior. Indeed, many researchers who have used the Theory of Planned Behavior as a foundation found that pro-environmental intentions predict subsequent environmental behavior (Chen, 2016;Dienes, 2015;Masud et al, 2016;van Riper et al, 2013;Xue et al, 2021), although some have found an intention-behavior gap for habitual behavior (e.g., Lin, 2013). Since pro-environmental intentions can be understood as a cause-related political topic, it is comprehensible that these intentions do not only predict traditional environmental behavior such as recycling, but-in response to influencers' online communication-also translate into action in the online realm stimulating more online political participation.…”
Section: Social Media Influencers and Environmental Mobilizationmentioning
confidence: 99%
“…Drawing from the Theory of Planned Behavior (Ajzen, 1985), which postulates that behavioral intentions need to be formed before individuals perform a behavior, it can be expected that environmental behavior intentions function as a predictor for subsequent behavior. Indeed, many researchers who have used the Theory of Planned Behavior as a foundation found that pro-environmental intentions predict subsequent environmental behavior (Chen, 2016;Dienes, 2015;Masud et al, 2016;van Riper et al, 2013;Xue et al, 2021), although some have found an intention-behavior gap for habitual behavior (e.g., Lin, 2013). Since pro-environmental intentions can be understood as a cause-related political topic, it is comprehensible that these intentions do not only predict traditional environmental behavior such as recycling, but-in response to influencers' online communication-also translate into action in the online realm stimulating more online political participation.…”
Section: Social Media Influencers and Environmental Mobilizationmentioning
confidence: 99%
“…Wei studied the emotional changes of the proximate residents caused by the new chemical plant using the structural equation model (SEM); the results show that the sense of unfairness and dissatisfaction with the government will increase the probability of environmental NIMBY events [ 17 ]. In addition, direct or indirect factors such as people’s risk perception [ 18 , 19 ], differential government trust [ 2 ], psychological acceptance [ 20 ], and the “emotional state” of proximate residents [ 21 ] will increase the probability of public resistance. The difference between the significant positive externalities of the NIMBY facilities to the grass-roots government and the negative externalities relative to the residents near the NIMBY facilities leads to the imbalance of benefit distribution [ 22 ].…”
Section: Literature Reviewmentioning
confidence: 99%